Stark images the documentary photography of Donald McCullin - Media Loft. (White Plains, N.Y.: The Center for Humanities, 1975)
Photographer Donald McCullin discusses his philosophy on photographing death and dying. Explains how he relates to suffering as a photographer and demonstrates how photography can be an effective agent of social change.
Editors, Nancy J. Buquoi, R. Smith Schuneman.
Keywords: McCullin, Don -- 1935-.; Photography, Documentary; Photographers; Art studies; Humanities